Cardiac computed tomography in infective endocarditis - Petković, Ana; Ivanovic, Branislava; Maksimovic, Ruzica (Medicinski podmladak, 2024)
Infective endocarditis is a rare disease with an increasing incidence and an unchanged high mortality rate, despite the rapid medical development. Imaging plays integrative part in diagnosis of IE, with echocardiography as main diagnostic test. Rising research data in utility of Cardiac Computed Tomography (CCT) in diagnostic algorithm of IE, indicates its importance in detection of IE-related lesion along with the exclusion of coronary artery disease. The latest 2023 European Society of Cardiology Guidelines in management of IE classified CCT as class of recommendation I and level of evidence B in detection of both valvular and paravalvular lesions in native and prosthetic valve endocarditis. This review article provides comprehensive and contemporary review of role of CCT in diagnosis of IE, optimization of acquisition protocols, morphology characteristics of IE-related lesions, published data of diagnostic performance of CCT in comparison to echocardiography as the state-of-art method, limitation and future possibilities.